A Quad-Element UWB-MIMO Antenna with Band-Notch and Reduced Mutual Coupling Based on EBG Structures - Wenjing Wu; Bo Yuan; Aiting Wu (International Journal of Antennas and Propagation)
A compact planar quad-element ultrawideband (UWB) antenna with a band-notch and low coupling for multiple-input multiple-output (MIMO) system is proposed in this paper. The antenna consists of four circular monopoles with modified defected ground plane and a periodic electromagnetic band gap (EBG) structures. The proposed EBG structures are modified from the traditional mushroom-like ones, comprised of patterns of grids on the top patch, the metallic ground plane, and several vias that connect the top and bottom plane. It is printed at the center of the dielectric substrate to lower electromagnetic coupling between the parallel elements. Besides, by etching four crescent ring-shaped resonant slots on the radiators, a sharp band-notched characteristic is achieved. From the experimental results, the −10 dB bandwidth of the antenna is extended covers from 3.0 to 16.2 GHz, with a sharp notched band at 4.6 GHz. And the isolation is greater than 17.5 dB between its elements, with a peak gain of 8.4 dB and a peak efficiency of 91.2%. Moreover, it has a compact size of 0.6λ×0.6λ×0.016λ at 3 GHz and could be a good candidate for portable devices.